Carbon-Rich Nanomaterials: Fascinating Hydrogen and Oxygen Electrocatalysts - Zhang, Jian; Chen, Guangbo; Muellen, Klaus; Feng, Xinliang (Advanced Materials, 2018)
Hydrogen energy is commonly considered as a clean and sustainable alternative to the traditional fossil fuels. Toward universal utilization of hydrogen energy, developing high-efficiency, low-cost, and sustainable energy conversion technologies, especially water-splitting electrolyzers and fuel cells, is of paramount significance. In order to enhance the energy conversion efficiency of the water-splitting electrolyzers and fuel cells, earth-abundant and stable electrocatalysts are essential for accelerating the sluggish kinetics of hydrogen and oxygen reactions. In the past decade, carbon-rich nanomaterials have emerged as a promising class of hydrogen and oxygen electrocatalysts. Here, the development and electrocatalytic activity of various carbon-rich materials, including metal-free carbon, conjugated porous polymers, graphdiyne, covalent organic frameworks (COFs), atomic-metal-doped carbon, as well as metal–organic frameworks (MOFs), are demonstrated. In particular, the correlations between their porous nanostructures/electronic structures of active centers and electrocatalytic performances are emphatically discussed. Therefore, this review article guides the rational design and synthesis of high-performance, metal-free, and noble-metal-free carbon-rich electrocatalysts and eventually advances the rapid development of water-splitting electrolyzers and fuel cells toward practical applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbon-rich nanomaterials; electrocatalysts; fuel cell; oxygen reduction; water splitting